Uncovering the Satisfying MOOC Gamification Elements via fuzzy Analytic Hierarchy Process - Hui Ling, Nie; Jen Chen, Chwen; Siong Teh, Chee (International Journal of Engineering and Technology, 2018)
The constantly high drop-out rate in MOOCs remains as a concern of many MOOC providers. Gamification elements in MOOCs are seen to be able to alleviate this problem. As satisfaction is crucial to sustain learners’ engagement in MOOCs, this study aims to uncover the satisfying gamification elements for MOOC via Fuzzy Analytical Hierarchy Process (FAHP) approach. The study reveals learner-learner interaction as a significant criterion to provide a sense of satisfaction among MOOC learners and the most satisfying gamification elements are leaderboard, badge and opponent and thus, should be considered to be incorporated into MOOCs.